LOCALIZED PAST, GLOBALIZED FUTURE: TOWARDS AN EFFECTIVE BIOETHICAL FRAMEWORK USING EXAMPLES FROM POPULATION GENETICS AND MEDICAL TOURISM - Widdows, Heather (Bioethics, 2011)
This paper suggests that many of the pressing dilemmas of bioethics are global and structural in nature. Accordingly, global ethical frameworks are required which recognize the ethically significant factors of all global actors. To this end, ethical frameworks must recognize the rights and interests of both individuals and groups (and the interrelation of these). The paper suggests that the current dominant bioethical framework is inadequate to this task as it is over-individualist and therefore unable to give significant weight to the ethical demands of groups (and by extension communal and public goods). It will explore this theme by considering the inadequacy of informed consent (the ‘global standard’ of bioethics) to address two pressing global bioethical issues: medical tourism and population genetics. Using these examples it will show why consent is inadequate to address all the significant features of these ethical dilemmas. Four key failures will be explored, namely, • That the rights and interests of those related (and therefore affected) are neglected; • That consent fails to take account of the context and commitments of individuals which may constitute inducement and coercion; • That consent alone does not have the ethical weight to negate exploitation or make an unjust action just (‘the fallacy of sufficiency’); • That consent is a single one-off act which is inappropriate for the types of decision being made. It will conclude by suggesting that more appropriate models are emerging, particularly in population genetics, which can supplement consent.